A 1-h time interval between a meal containing iron and consumption of tea attenuates the inhibitory effects on iron absorption: a controlled trial in a cohort of healthy UK women using a stable iron isotope - Ahmad Fuzi, Salma F; Koller, Dagmar; Bruggraber, Sylvaine; Pereira, Dora IA; Dainty, Jack R; Mushtaq, Sohail (The American journal of clinical nutrition, 2017)
Tea has been shown to be a potent inhibitor of nonheme iron absorption, but it remains unclear whether the timing of tea consumption relative to a meal influences iron bioavailability. The aim of the study was to investigate the effect of a 1-h time interval of tea consumption on nonheme iron absorption in an iron-containing meal in a cohort of iron-replete, nonanemic female subjects with the use of a stable isotope ( Fe). Twelve women (mean ± SD age: 24.8 ± 6.9 y) were administered a standardized porridge meal extrinsically labeled with 4 mg Fe as FeSO on 3 separate occasions, with a 14-d time interval between each test meal (TM). The TM was administered with water (TM-1), with tea administered simultaneously (TM-2), and with tea administered 1 h postmeal (TM-3). Fasted venous blood samples were collected for iron isotopic analysis and measurement of iron status biomarkers. Fractional iron absorption was estimated by the erythrocyte iron incorporation method. Iron absorption was 5.7% ± 8.5% (TM-1), 3.6% ± 4.2% (TM-2), and 5.7% ± 5.4% (TM-3). Mean fractional iron absorption was found to be significantly higher (2.2%) when tea was administered 1 h postmeal (TM-3) than when tea was administered simultaneously with the meal (TM-2) ( = 0.046). An ∼50% reduction in the inhibitory effect of tea (relative to water) was observed, from 37.2% (TM-2) to 18.1% (TM-3). This study shows that tea consumed simultaneously with an iron-containing porridge meal leads to decreased nonheme iron absorption and that a 1-h time interval between a meal and tea consumption attenuates the inhibitory effect, resulting in increased nonheme iron absorption. These findings are not only important in relation to the management of iron deficiency but should also inform dietary advice, especially that given to those at risk of deficiency. This trial was registered at clinicaltrials.gov as NCT02365103.